Penatalaksanaan Demam Tifoid pada Lansia dengan Pendekatan Kedokteran Keluarga - Dwi Jayanti Tri Lestari; Aila Karyus (MAJORITY, 2020)
Typhoid fever is a systemic infectious disease caused by Salmonella typhi bacteria that can enter through contaminated food and drink. According to CDC, the incidence of typhoid fever in The United States of America at the age group of 45-64 years old was 23 patients from the total of 309 patients. Early treatment and prevention of recurrence are important to prevent the worsening of the disease and its complications. This study is a case report. Primary data was obtained from autoanamnesis, physical examination and home visits. Secondary data was obtained from the patient's medical records at the public health center. The assessment is based on a holistic diagnosis from the beginning, process, and end of study quantitatively and qualitatively. Patient Mrs. P, 67 years old, has typhoid fever due to poor hygiene, but the patient still has a functional degree of 2 in carrying out daily activities. Patient had internal risk factors, which were poor personal hygiene and the lack of patient knowledge about typhoid fever. External factor was the lack of house cleanliness. Patient management was done with the implementation of patient-centered, family-focused, and community-oriented approach. The interventions given were secondary prevention of typhoid fever and education of a clean and healthy lifestyle carried out in three times visits. The evaluation resulted in less complaints of patient illness and more knowledge and attitudes of patients and families related to typhoid fever were gained.